If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrtx + -2 = x + -8 Reorder the terms: -2 + qrstx = x + -8 Reorder the terms: -2 + qrstx = -8 + x Solving -2 + qrstx = -8 + x Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + qrstx = -8 + 2 + x Combine like terms: -2 + 2 = 0 0 + qrstx = -8 + 2 + x qrstx = -8 + 2 + x Combine like terms: -8 + 2 = -6 qrstx = -6 + x Divide each side by 'rstx'. q = -6r-1s-1t-1x-1 + r-1s-1t-1 Simplifying q = -6r-1s-1t-1x-1 + r-1s-1t-1 Reorder the terms: q = r-1s-1t-1 + -6r-1s-1t-1x-1
| 8x-7=-3(-12x-1)+4(-7x-3) | | 8x-7=-3(-12-1)+4(-7x-3) | | x/3-88/3x=1 | | 4x^2+3x-200=0 | | 20(0.25)+14(3)+5(0.5)= | | -7/2x+16/4x=-2/4 | | 4x^2-3x-200=0 | | 35(0.25)+15(3)+5(0.5)= | | 3(1/2+1/2y)+2y=-9 | | 35(0.25)+14a+5b=49.5 | | 4x+15=25 | | 0=-z^3(9-z)+4z(2+3z) | | 20(0.25)+15a+5b=56.25 | | 0=m(5m-2)+9(5-m) | | 12+16+30/7 | | 0=2(3r^2+4r+2)-3(-r^2+4r-5) | | 2x+3=-23 | | 0=(3p+5)(3p+5) | | 3c+4u=33 | | 0=(x^4-3x^2+2)-(-2x^4+x^2-3) | | 2*60-60= | | 2(2x-7)+2x=22 | | =60+60 | | 0=(r+3)(r+3)(r+3)(r+3) | | 4*60-2*60= | | 4x-2*(60)+2x-(60)=180 | | 0=(z-3)(z-3)(z-3) | | 5p+3=14 | | (x-6)(x-4)=-16 | | 4x-2*(-60)+2x-(-60)=180 | | 0=[(2m+7)-n][(2m+7)-n] | | 0=9/16y-63 |